2008
DOI: 10.1016/j.jnoncrysol.2007.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Elastic properties and structural studies on lead–boro–vanadate glasses

Abstract: This paper describes elastic properties and spectroscopic studies on the xPbO-50B 2 O 3 -(50 -x)V 2 O 5 (where x = 20, 25, 30, 35, 40, 45 and 49 mol%) glass system. Elastic moduli and spectroscopic parameters exhibit compositional dependent trends and the existence of characteristic borovanadate groups in these glasses. The bulk modulus and shear modulus increase with the concentration of [BO 4/ 2 ] À and [B 2 V 2 O 9 ] 2À groups, which increases the dimensionality of the network. The scheme of modification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(8 citation statements)
references
References 23 publications
1
6
1
Order By: Relevance
“…It is suggested that in this condition, Fe 3 + ions may occupy interstitial positions and form strong covalent Fe\O bond [11,30] which may also contribute to the increase in rigidity of the glass. Generally, an increase in elastic moduli has been suggested to be related to the increase in BO, such as for the (90 − x)TeO 2 - [46]. However, in the present study, the observed initial large increase in independent moduli L and G and other related elastic moduli was not accompanied by a parallel large increase in BO.…”
Section: Discussioncontrasting
confidence: 83%
“…It is suggested that in this condition, Fe 3 + ions may occupy interstitial positions and form strong covalent Fe\O bond [11,30] which may also contribute to the increase in rigidity of the glass. Generally, an increase in elastic moduli has been suggested to be related to the increase in BO, such as for the (90 − x)TeO 2 - [46]. However, in the present study, the observed initial large increase in independent moduli L and G and other related elastic moduli was not accompanied by a parallel large increase in BO.…”
Section: Discussioncontrasting
confidence: 83%
“…Meanwhile, it is worth mentioning that the as-synthesized polycrystalline α-PbO nanosheets have mechanical characteristics in withstanding plastic deformability that lies in that high concentration grain boundaries in polycrystalline materials that can strengthen the mechanical properties through impeding the dislocation motion, hindering the continuity of slip from grain to grain [63]. This has been reported as mechanical reinforced component materials [64], which proposes guiding suggestions for future device fabrication. Moreover, the interlayer interaction energy in α-PbO nanosheets is as small as 0.016 eV atom −1 [13,14], energetically favouring layer sliding activated by nanoindentation force [65] which may easily occurred (figure S25), leading to the tendency that Young's modulus decreases with the increase of thickness.…”
Section: Resultsmentioning
confidence: 93%
“…All the synthesized glasses show two bands in the 1200-1600 cm −1 region, the first one with a maximum at 1332 cm −1 is attributed to the B–O vibration in BO 3 [ [53] , [54] , [55] , [56] , [57] ]. The second located at 1232 cm −1 could be attributed to the trigonal bending of boron in the diborovanadate groups [B 2 V 2 O 9 ] 2- [ 44 , 58 , 59 ]. Noting that with increasing the concentration of the V 2 O 5, this peak becomes more intensive and increases from 1207 to 1232 cm −1 .…”
Section: Resultsmentioning
confidence: 99%